The 2023-2026 Hospice and Palliative Nurses Association Research Agenda. Issue 2 (April 2023) - Coats, Heather; Doyon, Katherine; Isaacson, Mary J.; Tay, Djin; Rosa, William E.; Mayahara, Masako; Kates, Jeannette; Frechman, Erica; Wright, Patricia Moyle; Boyden, Jackelyn Y.; Broden, Elizabeth G.; Hinds, Pamela S.; et al.
Abstract : The Hospice and Palliative Nursing Association established the triannual research agenda to ( a ) provide focus for researchers to conduct meaningful scientific and quality improvement initiatives and inform evidence-based practice, ( b ) guide organizational funding, and ( c ) illustrate to other stakeholders the importance of nursing research foci. HPNA Research Agendas are developed to give direction for future research to continue advancing expert care in serious illness and ensure equitable delivery of hospice and palliative care.